Service Marketing Mix Factors that Influence the Decision to Buy Uniqlo Apparel in Pathum Thani - Chienwattanasook, Krisada; Prechachan, Chanikan; Masomboon, Wimonmas; Wongvanich, Boontharika (Journal of Management Science Nakhon Pathom Rajabhat University, 2024)
The purpose of this study is to investigate the components of the service marketing mix (7Ps) that influence consumers’ purchase decisions for Uniqlo brand apparel in Pathum Thani Province. The sample group used for this study consists of 418 consumers in Pathum Thani province who purchased Uniqlo brand apparel. The data was collected using questionnaires and a non-probability purposive sampling method. Statistical methods used for data analysis include percentages, means, standard deviations and a Partial Least Square Structural Equation Model (PLS-SEM). The research results show that the elements of service marketing mix, namely product, promotion, and process, significantly influence consumers’ purchase decisions for Uniqlo brand apparel in Pathum Thani province, with statistical significance levels of .043, .000 and .009, respectively. These three variables together account for 55.5 percent of the predictive accuracy. Article history: Received 26 May2023 Revised 1 December 2023 Accepted 4 December 2023 SIMILARITY INDEX = 4.32 %